Production of wild ginger (siphonochilus aethiopicus) under protection and indigenous knowledge of the plant from traditional healers - Du Toit, Elsie Sophia (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Horticulture))--University of Pretoria, 2007.